Derivation of Curve Numbers from the Observed Rainfall and Runoff Data for Banha and Karso Watersheds of Upper Damodar Valley in Jharkhand State - Rao, B. Krishna; singh, D.K.; Bhattacharya, A.K.; Singh, A. (Journal of Soil and Water Conservation, 2022)
Runoff quantification is an important activity in designing soil and water conservation measures, water harvesting structures and watershed management programmes. A widely used method of runoff estimation developed by USDA- SCS uses rainfall depth and Curve Number and known as Curve Number (CN) method. The method was developed based on individual rainfall events and availability of this data is limited. Therefore, there is necessity to derive the curve numbers for given watershed and land uses from the daily rainfall and runoff data. In this direction, a study was conducted to deriving curve numbers from observed event-based and 24—hr period duration rainfall and runoff data for Banha and Karso watersheds in Upper Damodar Valley (UDV), Jharkhand. The derived CN values from event-based rainfall and runoff for AMC-II condition were estimated to be 88 and 86 for Banha and Karso watersheds respectively. The closeness between derived CN and handbook CN indicate that CNs for runoff estimation for individual events may be selected from handbook tables. The derived CN values from daily rainfall and runoff for AMC II were estimated to be 80 and 78 for Banha and Karso watersheds respectively. The average absolute deviations between runoff estimated by using derived Curve Numbers and observed runoff was too small. This indicate that the derived Curve Numbers for Banha and Karso can be used for runoff estimation from event based and daily rainfall.